Reproductive investment and multiple spawning evidence in the redfinger rubble crab Eriphia gonagra (Brachyura, Eriphioidea) - Teixeira, Gustavo M.; Fransozo, Vivian; Góes, João M.; Fernandes-góes, Lissandra C.; Hirose, Gustavo L.; Almeida, Ariádine C.; Fransozo, Adilson (Sociedade Brasileira de Carcinologia, 2017)
Abstract The variation in reproductive investment (RI) and the hypothesis of multiple spawning were evaluated in the redfinger rubble crab Eriphia gonagra (Fabricius, 1781). The gonads and embryos showed synchronous development, and fecundity and RI varied widely among females of the same size class. The mean RI value recorded was 11.31%, with no significant differences among the means for different size classes. The allometric analysis of fecundity indicated RI decrease while body size increase, but we suggested that this occurs due to size overestimation where the largest width of carapace was used as body size reference in these analyzes. In addition, we found an isometric relationship for “female weight vs. egg number”, and also for “female weight vs. egg weight”, indicating that RI ​​increased proportionally with size of females. Relatively high frequencies both of smaller females with rudimentary gonads, and of larger females with developed gonads were observed. This indicates that larger females take place more frequently in the population reproductive output over time. This difference could not be observed by means of RI analyses of captured and fixed crabs, for which only one stage of gonad development and/or one spawning is usually recorded.
Keywords: Decapoda; allometric analysis; fecundity; reproductive effort